Shedding light inside the black box of implementation: Tax crimes as a predicate crime for money laundering. Issue 3 (21st May 2021) - Rossel, Lucia; Unger, Brigitte; Ferwerda, Joras
Abstract: Even perfect transposition of EU Directives does not necessarily translate into homogeneous rules or application of rules across the European Union. Europeanization literature focused on the formal transposition of EU Directives. Newer studies suggest looking into the black box of how this translates into law in action. The 4th Anti‐Money Laundering Directive incorporated taxes as a predicate crime for money laundering. We analyze how and why this Directive has been implemented so differently across EU countries both in the books and in action through a novel dataset. We find that country characteristics can explain formal transposition patterns and influence the domestic adaptation of regulation as well as how practitioners, the second front line of implementation, use these rules in action. We find that corruption, government effectiveness, regulatory quality, tax morale, and tax administrative capacity are important factors to explain lingering differences in the books and in action among EU Member States.